Tax Progressivity and Tax Evasion - Laszlo Goerke (Center for Economic Studies and ifo Institute (CESifo), 2003)
More progressive income taxes raise employment in models of imperfectly competitive labour markets. However, this prediction is not robust to modifications of the analytical structure. For example, in an efficiency wage setting, more progressive taxes reduce profits. This induces firms to exit the market such that the positive employment effect can vanish in a framework with a constant profit constraint. In this paper, it is demonstrated for an according model that tax evasion opportunities raise the likelihood of positive employment effects due to higher tax progressivity.
Keywords: 330; efficiency wages; employment; income tax; tax evasion; tax progressivity